Urogenital tract and rectal microbiota composition and its influence on reproductive outcomes in infertile patients - Dong, Yong-Hong; Fu, Zhong; Zhang, Ning-Nan; Shao, Jing-Yi; Shen, Jie; Yang, En; Sun, Shi-Yi; Zhao, Zhi-Min; Xiao, An; Liu, Chen-Jian; Li, Xiao-Ran (Frontiers in Microbiology, 2023)
Microbiota in the human body are closely related to human diseases. Female urogenital tract and rectal microbes have been considered as important factors affecting female pregnancy, but the mechanism is unknown. Cervical, vaginal, urethral, and rectal swabs were collected from 22 infertile patients and 10 controls, and follicular fluid was extracted from 22 infertile patients. The microbial composition of different sampling sites of infertile patients was examined. By comparing the microbial composition difference between infertile patients and controls and combining bioinformatics methods to analyze the potential impact of the female urogenital tract (cervical, vaginal and urethral) and rectal microbial diversity on female infertility and pregnancy outcomes. Lactobacillus predominated in the female urogenital tract, but its abundance decreased in infertile patients, whereas the abundance of Gardnerella and Atopobium increased. The microbial changes in the urethra had the same trend as that in the vagina. Compared with healthy controls, the cervical and rectal microbial diversity of infertile patients were significantly increased and decreased, respectively. There might be interactions between microbes in different parts of female. Geobacillus thermogeniticans was enriched in the urogenital tract and rectum of infertile patients, and has a good predictive effect on infertility. Compared with infertile patients, L. johnsonii was enriched in the vagina, urethra, and intestine of the control group. L. acidophilus in follicular fluid might be associated with Non-pregnancy. This study found that the microbial composition of infertile patients was changed compared with that of healthy people. The translocation of Lactobacillus between the rectum and urogenital tract might play a protective barrier role. The changes of Lactobacillus and Geobacillus might be related to female infertility or pregnancy outcome. The study provided a theoretical basis for the future treatment of female infertility from the perspective of microorganisms by detecting the microbial changes associated with female infertility.